Desulphurization of FGD wastewater through bacterial sulfate reduction process with agricultural incineration bottom ash as an amendment. (June 2022) - Yan, Jia; Liu, Shinian; Bao, Min; Xie, Jiehui; Yang, Jinbin; Zheng, Qiunan; Lin, Xun; Li, Jiajun; Lu, Qihong; Li, Shugeng; Zhang, Hongguo
Abstract: Coal-fired power plants produce a large amount of sulfate-laden flue gas desulphurization (FGD) wastewater, while a sustainable amount of incineration ash was produced as solid waste in biomass power plants. Both FGD wastewater and incineration ash led to serious environmental problems without proper treatment. Sulfate reduction was an efficient technology for FGD wastewater treatment, however, the carbon source was insufficient for reducing sulfate in FGD wastewater which needed to be replenished. In this study, pyrolyzed incineration bottom ash (PIA) was introduced to sulfate reducers for FGD wastewater treatment. Sulfate-reducing activity increased (up to 2.9-fold) with PIA300 (incineration ash pyrolyzed under 300 °C) addition. Remarkably increasing abundance of Clostridium (12-fold) and Paraclostridium sp. (79-fold) bacteria were observed in sulfate-reducing sludge with PIA300 addition. Pyrolyzed incineration ash not only acted as a carrier for sulfate reducers, but also provided additional carbon, alkalinity and trace elements (Fe, K, Ca, etc.) for sulfate reduction. Incineration ash was partially degraded by sulfate-reducing bacteria (up to 39.4%), meanwhile, heavy metals (Mg, Al, Cr, Co, Ni, Cu, Zn, etc.) leached from ash and existed in FGD wastewater were efficiently co-removed (95–100%). Addition of PIA to sulfate reducers led to increased formation of extracellular polymeric substances, which might enhance the biotransformation and degradation of organic matters in both ash and FGD wastewater. Thus, a promising FGD wastewater treatment technology was established in this study, to achieve simultaneous FGD wastewater reclaim and solid waste utilization. Graphical abstract: Unlabelled Image Highlights: Pyrolyzed incineration ash (PIA) was introduced to sulfate-reducing bacteria. Sulfate-reducing activity increased 2.9-folds after addition of PIA300. PIA300 played as carrier, carbon and nutrient sources during sulfate reduction. PIA addition remarkably decreased operation cost for FGD wastewater treatment.